Processes of Startup Clusters Formation – Analysis of Chosen Case Studies - Klaudia MIGASIEWICZ; Michał ORGANA (Communications of International Proceedings, 2021)
Startup clusters are one of the potential spaces for the development of modern startups. To become attractive, they should ensure the best possible quality consisting of many different factors, about which the first decisions can be made at the stage of creating the cluster. Therefore, the processes of creating startup clusters have been discussed in this article. The essence of startup clusters functioning was presented, and the processes of their formation were described. They have been characterized: the bottom-up and top-down approaches of the startup clusters formation. The authors also provided examples of factors influencing the clustering process. Then, using two case studies, they described the processes of creating startup clusters operating in Poland. Based on the conducted analyzes, further research proposals on this topic were proposed.
Keywords: Startup; cluster; startup cluster; cluster formation process